HIV Among People Who Inject Drugs in Central and Eastern Europe and Central Asia : A Systematic Review with Implications for Policy - Jolley, Emma (BMJ Publishing Group, 2015)
HIV among people who inject drugs (PWID) is a major public health concern in Eastern and Central Europe and Central Asia. HIV transmission in this group is growing and over 27 000 HIV cases were diagnosed among PWID in 2010 alone. The objective of this systematic review was to examine risk factors associated with HIV prevalence among PWID in Central and Eastern Europe and Central Asia and to describe the response to HIV in this population and the policy environments in which they live.